2015
DOI: 10.3151/jact.13.489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mineral Admixtures on Pipe Flow of Pumped Concrete

Abstract: The objective of this study is to investigate the effect of the mineral admixtures on pipe flow of pumped concrete through analyzing the properties of lubrication layer playing a dominant role to facilitate concrete pumping. Concrete mixtures incorporating blast furnace slag (BFS), fly ash (FA) and silica fume (SF) were selected with three different replacement ratios for each case and pumped through 170 m circuit. The rheological properties were measured before pumping and the thickness of lubrication layer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The constitutive mortar was obtained by screening the fresh concrete. The measurement applied was improved following the method proposed in [ 24 , 27 ]. A Viskomat XL coaxial rheometer, which has a four-bladed vane of the height ( h 1 ) of 70 mm and radius ( R i ) of 35 mm, was utilized to carry out the rheological measurement of samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The constitutive mortar was obtained by screening the fresh concrete. The measurement applied was improved following the method proposed in [ 24 , 27 ]. A Viskomat XL coaxial rheometer, which has a four-bladed vane of the height ( h 1 ) of 70 mm and radius ( R i ) of 35 mm, was utilized to carry out the rheological measurement of samples.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the lubrication layer is usually considered to be the constitutive mortar of fresh concrete. Some researches indicated that the yield stress and viscosity of the lubrication layer are small compared with that of bulk concrete, but the rheological properties of the lubrication layer directly determined the pressure loss along the pumping process [ 27 ]. Some authors have found that the thickness of the lubrication layer was about 2 mm through the measurement with ultrasonic velocity profiler, which may depend on the volume fraction of aggregate and the diameter of the pump pipe [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the lower the water-binder ratio, the thinner the lubricating layer. An Ultrasonic Velocity Profiler (UVP) was used to monitor the thickness of lubricating layer and measure the velocity of concrete cross section in the full size pumping circuit with or without adding mineral admixtures [12][13][14][15]. Another technique reported in literature [16] with particle image velocimetry (PIV) was applied to estimate the velocity profile along the cross section of concrete flowing in a half open pipe test configuration.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber extracted from Cocos nucifera (coconut), treated as drag-reducing agent in aqueous media flow, was used to reduce friction in pipe flow, which created a huge profit for the pipeline company [30]. Myoung investigated the effect of the mineral admixture on pipe flow of pumping concrete through analyzing the properties of lubricating layer and noted that the usage of blast furnace and silica fume having 5% replacement could increase efficiency of pumping concrete [12].…”
Section: Introductionmentioning
confidence: 99%